Strategic corporate finance : applications in valuation and capital structure - Pettit, Justin, 1965- (Wiley finance series., 2007)
Essential guidance for the corporate finance professional -- advisor, Board Director, CFO, Treasurer, business development executive, or M & A expert--to ask the right questions and make the critical decisions. Strategic Corporate Finance is a practical guide to the key issues, their context, and their solutions.